2021
DOI: 10.3389/fimmu.2021.771766
|View full text |Cite
|
Sign up to set email alerts
|

The Second Study of Clinical and Immunological Findings in Anti-laminin 332-Type Mucous Membrane Pemphigoid Examined at Kurume University—Diagnosis Criteria Suggested by Summary of 133 Cases

Abstract: BackgroundRecently, we published an article retrospectively summarizing the results in 55 anti-laminin 332 (LM332)-type mucous membrane pemphigoid (MMP) cases examined at Kurume University, which were diagnosed by strict inclusion criteria, including positive reactivity in direct immunofluorescence and absence of antibodies to non-LM332 autoantigens. However, indirect immunofluorescence using 1M-NaCl-split normal human skin (ssIIF) is also valuable for diagnosis of anti-LM332-type MMP.MethodsIn this second stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…For diagnosis of autoimmune bullous diseases, there is a certain false negative rate of direct immunofluorescence, particularly for MMP. Actually, in our recently published paper, the positive rate of direct immunofluorescence in anti-LM332-type MMP was 89.8% (88 in 98 cases) ( 10 ).…”
Section: Discussionmentioning
confidence: 85%
“…For diagnosis of autoimmune bullous diseases, there is a certain false negative rate of direct immunofluorescence, particularly for MMP. Actually, in our recently published paper, the positive rate of direct immunofluorescence in anti-LM332-type MMP was 89.8% (88 in 98 cases) ( 10 ).…”
Section: Discussionmentioning
confidence: 85%
“…Among these mucosal sites, oral mucosa is affected most frequently, followed by ocular mucosa, with other mucosal sites involved less frequently [ 21 ]. In our latest study, which included 133 anti-LM332-type MMP patients, 89% had oral lesions, 43% had ocular lesions, 19% had pharyngeal lesions, 15% had laryngeal lesions, 11% had genital lesions, 6% had nasal lesions and 3% had esophageal lesions [ 22 ]. Compared with other types of MMP, the oral and ocular mucosae were involved more commonly and seriously in patients with anti-LM332-type MMP [ 23 ].…”
Section: Clinical and Histological Features Of Anti-lm332-type Mmpmentioning
confidence: 99%
“…Moreover, oral destructions may result in airway obstruction, whereas the involvement of ocular mucosa usually includes scarring; these complications may lead to mortality and blindness, respectively [ 24 ]. The presence of skin lesions is not a necessary condition for the diagnosis of anti-LM332-type MMP, although more than 60% of patients present with skin involvement [ 12 , 22 , 24 , 25 ].…”
Section: Clinical and Histological Features Of Anti-lm332-type Mmpmentioning
confidence: 99%
“…Ln-332, formerly known as kalinin, epiligrin, nicein and laminin-5, is a heterotrimer, which is the most important for the skin integrity. 3 Beyond the adhesion function, Ln-332 is associated with cell migration, tissue maturation, and wound repair. Ln-332 consists of the laminin chains (subunits) α3 (165 and 145 kDa), β3 (140 kDa) and γ2 (105 kDa).…”
Section: Introductionmentioning
confidence: 99%
“…Ln-332 consists of the laminin chains (subunits) α3 (165 and 145 kDa), β3 (140 kDa) and γ2 (105 kDa). 3 , 4 By analyzing the immune profile of MMP patients, it was reported that the IgG was mostly directed to the α3 subunit (86%), followed by the β2 subunit (46%) and the γ2 subunit (29%). 7 Huang et al 8 revealed the distinct roles of the three Ln-332 subunits (α3, β3 and γ2) in cell proliferation, migration, invasion and apoptosis.…”
Section: Introductionmentioning
confidence: 99%